2014
DOI: 10.1242/dev.114728
|View full text |Cite|
|
Sign up to set email alerts
|

A transcription factor network specifying inhibitory versus excitatory neurons in the dorsal spinal cord

Abstract: The proper balance of excitatory and inhibitory neurons is crucial for normal processing of somatosensory information in the dorsal spinal cord. Two neural basic helix-loop-helix transcription factors (TFs), Ascl1 and Ptf1a, have contrasting functions in specifying these neurons. To understand how Ascl1 and Ptf1a function in this process, we identified their direct transcriptional targets genome-wide in the embryonic mouse neural tube using ChIP-Seq and RNA-Seq. We show that Ascl1 and Ptf1a directly regulate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…To determine whether Pax6 binds this enhancer, ChIP-qPCR was performed on caudal neural tube tissues from E11.5 embryos using an anti-Pax6 antibody (Coutinho et al, 2011) and primers that span the identified potential Pax6 binding sites. This region was found to be significantly enriched compared with a negative control region (Kirrel2) (Borromeo et al, 2014) (supplementary material Fig. S8).…”
Section: Cloning and Expression Of Xenopus Chicken And Amphioxus Prdmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether Pax6 binds this enhancer, ChIP-qPCR was performed on caudal neural tube tissues from E11.5 embryos using an anti-Pax6 antibody (Coutinho et al, 2011) and primers that span the identified potential Pax6 binding sites. This region was found to be significantly enriched compared with a negative control region (Kirrel2) (Borromeo et al, 2014) (supplementary material Fig. S8).…”
Section: Cloning and Expression Of Xenopus Chicken And Amphioxus Prdmentioning
confidence: 99%
“…ChIP was essentially conducted in mouse (Borromeo et al, 2014) and in Xenopus as described (Ma et al, 2014;Colin et al, 2011) (see supplementary material methods). RNAseq and ChIP data have been deposited at GEO under accession GSE64551.…”
Section: Rna Sequencing and Chromatin Immunoprecipitationmentioning
confidence: 99%
“…Furthermore, WM OPCs can proliferate in response to the growth factor PDGF but GM OPCs cannot (Hill et al, 2013). Given that the function of Ascl1 in the CNS is highly dynamic and context dependent (Helms et al, 2005;Mizuguchi et al, 2006;Wildner et al, 2006;Jacob et al, 2013), and that Ascl1 has been shown to regulate a complex set of downstream targets Borromeo et al, 2014), it is possible that Ascl1 in the oligodendrocyte lineages directly contributes to the differences in their intrinsic properties in the GM and WM.…”
Section: Ascl1 Is Required To Balance the Number Of Gm And Wm Astrocymentioning
confidence: 99%
“…6 R, S), although in early rh7 ( Fig. 2 A, C,J ) as well as in the spinal cord Hori et al, 2008;Borromeo et al, 2014) and cerebellum (Millen et al, 2014) Ptf1a-expressing progenitors produce Pax2 ϩ neurons but are not a significant source of Lmx1b ϩ neurons. In Ptf1a Ϫ/Ϫ rh7, Pax2 ϩ dBLa neurons were absent, while dBLb neurons significantly increased in number (ϳ1.8-fold compared with controls, p ϭ 0.0011; Fig.…”
Section: During Late Neurogenesis In Ptf1amentioning
confidence: 94%